Everyday engineering : how engineers see. - IDEO; Burroughs, Andrew, ....- (San Francisco : Chronicle Books, 2007)
World-renowned design and innovation firm IDEO uses first-hand observations to inform and inspire its work. Once again, as it did with the groundbreaking observational primer, "Thoughtless Acts? IDEO" brings its instructive methods to bear on the world around us, this time with an eye toward the inherent but unheralded presence of modern engineering. By observing the built environment we walk through every day - the often-overlooked details of buildings and roads, the joinings and interfaces of our infrastructure - we can learn to see the world as engineers do, and adapt this perspective to everyday thinking. Through simple pictures of how objects and environments behave over time, "Everyday Engineering" instructs anyone in creative fields, business, and design to see the world through IDEO's eyes.
Keywords: Industrieel ontwerpen